2016
DOI: 10.1097/md.0000000000002711
|View full text |Cite
|
Sign up to set email alerts
|

TNM Staging of Colorectal Cancer Should be Reconsidered According to Weighting of the T Stage

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 21 publications
(30 reference statements)
2
44
0
Order By: Relevance
“…The Finnish electronic medical records system tracks every patient until death, ensuring that no patients in this study were lost during follow-up. The 5-year survival rates in this study are comparable to those in larger studies reported previously [13,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 81%
“…The Finnish electronic medical records system tracks every patient until death, ensuring that no patients in this study were lost during follow-up. The 5-year survival rates in this study are comparable to those in larger studies reported previously [13,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 81%
“…It is well accepted that poorly differentiated and moderately differentiated carcinomas have worse prognoses than high differentiation carcinoma 27 . TNM staging is a classic evaluation of prognostic criteria, and the patients with stage III and IV have a worse prognosis than patients with TNM I and II 28 . In summary, hsa_circ_0067934 may represent a potential biomarker for assessing the risk of esophageal cancer and could function as a marker of ESCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The average standardized nomo-score of each TN combination from the three nomograms was then calculated. After ranking the average standardized nomo-score, we planned to divide the 25 TN combinations into five groups (I, II, IIIa, IIIb and IIIc) to be in consistence with previous studies [ 4 , 5 ]. As we found 5 stage groups would make the staging model simplest to analyze while still retain the survival paradox.…”
Section: Methodsmentioning
confidence: 99%
“…This study showed that T stage affected postoperative survival more significantly than N stage in non-metastatic colorectal cancer, and the survival paradox was also eliminated by adopting the T-plus staging system [ 4 ]. This staging system was verified by a Chinese cohort with 25-year follow-up [ 5 ]. However, the implemented process of this research applied linear regression, while the effect of TN combinations on survival may be non-linear.…”
Section: Introductionmentioning
confidence: 99%